Evolution of the Grasses x) - T. E. Soderstrom (BERITA BIOLOGI, 1968)
Because the flowers of grassos are so reduced, botanists in past have relied mostly on vegetative characters, such as the spikelets and their disposition in the inflorescence,to classify the family.Hackel,in his treatment of the Gramineae in Die Naturlichen pflanzen familien (late 1800'S proposed 12 tribes based on these characteristies and regarded the tribe.